Johann Heinrich Alsted e a árvore dos conhecimentos no século XVII - Fischer, Catarina Justus (2012)
Johannes Heinrich Alsted (1588-1638), a Calvinist scholar from Hesse, which at that time was a part of the Holy Roman Empire was the reputed author of Encyclopaedia Septem Tomis Reserata. Due to the singular historical context within which his life and works developed, he was taught by several important theologians, philosophers, linguists and mathematicians belonging with the German-Calvinist contemporary network. Nevertheless, he appealed to the Aristotelian tradition, Raymond Lull and Petrus Ramus as main sources to build his own method for a systematic approach to knowledge. Since his main concern was with pedagogy, Alsted s method sought to make learning easier, and for this purpose he appealed to the concept of encyclopedia. The present study analyzes the multiple sources employed by Alsted to elaborate a Tree of Knowledge of his own, and the fundamental epistemic and methodological principles that underpin a project that culminated in the renowned Encyclopaedia. Special attention was paid to the section on music taken as study case, in order to understand better the internal structure as well as the historical-scientifically determinants of this extraordinary work